PRODUCTION EFFICIENCY ANALYSIS KUB CHICKEN IN TEBING TINGGI - Tampe Tuah Malem Ginting; Tayi Supriana; Ma'ruf Tafsin (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
Efficiency is a measurement scale of a business or company in carrying out production activities. Tebing Tinggi City is one area that has potential in developing KUB Chicken cultivation. The purpose of this research was to analyze the level of technical, allocative and economic efficiency of KUB chicken farming activities in Tebing Tinggi City. Factors that affect production are as follows: DOC, Cage Area, Feed intake, OVK, Labor, while the dummy variables are the number of depletion and the quality of feed. Based on the research results, breeders in Tebing Tinggi City can be categorized as inefficient breeders In measuring the value of technical efficiency using Frontier 4.1 software where the results show have not been maximized where the overall average value of technical efficiency is 0.89, this means that all sample breeders are categorized as not being technically efficient because the efficiency value is still low. below the standard technical efficiency value of 1The same thing happened with the allocative and economic efficiency values of 0.17 and 0.19, this means that all sample farmers have not been categorized as allocative and economically efficient breeders where the allocative and economic efficiency standard value is 1. This condition can illustrate that there are still opportunities to increase production.